Lamination process evaluation of corn endosperm by process capacity indexes - Valdiviezo M, Martha (2009)
The objective of this study was to evaluate the perfomance of the process of lamination of the endosperm of corn in an agricultural company by means of the capability indices of processes, (PCI), low two focuses: traditional and bayesian. Both PCI was evaluated with simulated data under different suppositions. To the real case the results obtained by the bayesian PCI were Ĉb (D) = 0,81, while the traditional was Ĉp = 0,46 and Ĉpk = 0,81. It is concluded that the process of lamination is not capable. With regard to the simulated data, the results correspond to 100 samples of size 50, under three conditions: 1) the process is capable, centered and normal distributed. 2) It not process capable, not centered and normal. 3) The process is lightly capable, not centered and normal. Being concluded that so much in the condition 1 as in the 2, it is obtained that the index bayesian is smaller than the traditional index; while in the condition 3 is bigger than the traditional index.